compactness on bitopological spaces - Naser Majeed, Rasha (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this paper we define a new kind of open sets in bitopological space which we called semi open sets, which we lead to define a new type of compactness on bitopological spaces called "compactness" and we study the properties of this spaces, also we define the continuous functions between these spaces.